2011
DOI: 10.1155/2011/960583
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Meditation for Work Stress, Anxiety and Depressed Mood in Full‐Time Workers

Abstract: Objective. To assess the effect of meditation on work stress, anxiety and mood in full-time workers. Methods. 178 adult workers participated in an 8-week, 3-arm randomized controlled trial comparing a “mental silence” approach to meditation (n = 59) to a “relaxation” active control (n = 56) and a wait-list control (n = 63). Participants were assessed before and after using Psychological Strain Questionnaire (PSQ), a subscale of the larger Occupational Stress Inventory (OSI), the State component of the State/Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 33 publications
(26 reference statements)
2
72
1
2
Order By: Relevance
“…According to the Yoga Sutras of Patanjali, one of the oldest recorded scriptures on meditation, ''Yoga is the suppression of the modifications of the mind" (Rubia, 2009;Kokodoko, 2014) . Meditation has been proposed as a therapy for stress, anxiety, depression and other mental disorders which are typically characterized by problems with affective and attention systems (Rubia, 2009;Manocha et al, 2011;Platt et al, 2016). Meditation has important advantages compared with other therapies including lack of side effects compared to pharmacological treatments, costeffectiveness in sanitary programs, ease of implementation, and no need for complex instrumentation, technology or infrastructures.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Yoga Sutras of Patanjali, one of the oldest recorded scriptures on meditation, ''Yoga is the suppression of the modifications of the mind" (Rubia, 2009;Kokodoko, 2014) . Meditation has been proposed as a therapy for stress, anxiety, depression and other mental disorders which are typically characterized by problems with affective and attention systems (Rubia, 2009;Manocha et al, 2011;Platt et al, 2016). Meditation has important advantages compared with other therapies including lack of side effects compared to pharmacological treatments, costeffectiveness in sanitary programs, ease of implementation, and no need for complex instrumentation, technology or infrastructures.…”
Section: Introductionmentioning
confidence: 99%
“…11,19 Studies have shown that meditation has health benefits, [20][21][22] and studies have also shown that contribution of postures in maintaining health and fitness is small to insufficient. [23][24][25][26] However, with one exception, 27 literature does not document research that compares and contrasts the utilities of postures, breathing exercises, and mediation in health promotion or disease management.…”
Section: Relative Contribution Of Componentsmentioning
confidence: 99%
“…Many of Moody's (1992) 25 volunteers reported the healing and "smoothing over" (p. 113) of relationships as a result of discussing their lost loved one and sitting in a darkened, private enclosure; 12 experienced visions of the deceased and did not cognitively question the validity of the unusual sensory perceptions or eidetic imagery seen in and around the mirror. Research on elements that comprise the process, including scrying-an ancient information-accessing technique involving gazing into a reflective surface (Besterman, 1924(Besterman, /2005)-sensory deprivation (Bood, Sundequist, Kjellgren, Nordstrom, & Norlander, 2007;van Dierendonck & te Nijenhuis, 2005), and meditation (Lane, Seskevich, & Pieper, 2007;Manocha, Black, Sarris, & Stough, 2011) helps to explain the effects found during subsequent psychomanteum research (e.g., Arcangel, 1997;Radin & Rebman, 1996) to Moody's (1992) initial exploration, but it was Roll (2004), Hastings et al (2002), and Hastings (2012a) who directly investigated the psychomanteum's impact on psychological stress and painful emotions in the context of bereavement. Roll (2004) led 57 participants through a process involving a psychomanteum chamber and structured day of activities, including conversations about the deceased and a relaxing nature walk.…”
Section: International Journal Of Transpersonal Studiesmentioning
confidence: 99%
“…To control for sources of stress besides culture shock, participants who had experienced trauma within the prior year, including a psychiatric condition, hospitalization for a major illness or birth of a first child, sexual or physical abuse, or the death of a close loved one within the prior 6 months were screened-out with a short survey (e.g., Manocha et al, 2011). Respondents who drank more than three alcoholic beverages per day were also excluded, since excessive alcohol consumption may impair or delay recovery from emotional distress.…”
Section: International Journal Of Transpersonal Studiesmentioning
confidence: 99%